THE DEVELOPMENT OF SPORT IN THE USA - Toshmurodova E'zozaxon; Hakima Botirova (Лучшие интеллектуальные исследования, 2023)
Annotation:Sport development in the USA has been a significant focus over the years, with various organizations and initiatives working to promote and enhance the growth of sports at all levels. The United States Olympic Committee (USOC) plays a crucial role in supporting and developing athletes through its programs, including the Olympic Development Program and the Athlete Career and Education Program. Additionally, the National Collegiate Athletic Association (NCAA) provides opportunities for student-athletes to compete at the collegiate level, while also emphasizing the importance of academic success.